Teaching English for Young Learners (Early Childhood) in Kamal’s Kindergarten - Ulvia Ika Surya; Zakiyatul Mufidah (Universitas Trunojoyo Madura, 2023)
This study aims to determine effective methods for early childhood English learning. The sample of the research is consisted of 35 kindergarten children aged 4-5-6, who do not speak English and have no linguistic or speaking problems. The sample of the research consisted of six girls and seven boys aged 4, five girls and six boys aged 5, and seven girls and four boys aged 6. None of the children in the sample of research has had English education before. English language education in early childhood is of great importance since it makes children realize different languages and grow up with a positive attitude for English. Because of this reason, the most effective educational environment must be prepared for obtaining the most effective performance in English language education. The instructor needs to have adequate knowledge and background for the English language education and formation on early childhood. One of the most important facts about children’s learning a second language is the usage of that second language actively in the children’s environment. Such as the one in this study, many schools give English language education. Nevertheless, children can forget what they have learned since they are not using the second language actively in the daily life.